Peluang Zakat Maal sebagai Sumber Penerimaan Negara dalam APBN Indonesia - Minarni Minarni (Valid: Jurnal Ilmiah, 2020)
This research aims to examine the opportunity of zakat maal as a source of state revenue in the state budget (APBN) and the mechanism to be integrated with fiscal policy in Indonesia. Zakat is income distribution instrument that is highly remommended in Islamic teachings. The majority of Indonesians are Moslem so it has great potential to achieve the accumulation of funds sourced from zakat. Zakat maal in Indonesia can increase state revenue and help government expenditure. Furthermore, zakat also plays a role in increasing economic growth, public welfare and minimizing the state budget deficit. Opportunity for zakat maal as a state fiscal instrument can be realized through one-stop payment mechanism under authority of the Ministry of Finance. As for the distribution of zakat to the mustahik implemented in accordance with the provisions of the al Qur'an through government appointed institutions. This study use library research with qualitative descriptive analysis. The results of this research indicate zakat maal has a great opportunity as an element of state revenue and can be used as a source of state revenue in accordance with zakat and state finance regulations in Indonesia. The mechanism for accepting zakat maal into APBN can be pursued by providing a special zakat account code as a state revenue post.